Effects of Eccentric Overload Bout on Change of Direction and Performance in Soccer Players - de Hoyo, M.; de la Torre, A.; Pradas, F.; Sañudo, B.; Carrasco, L.; Mateo-Cortes, J.; Domínguez-Cobo, S.; Fernandes, O.; Gonzalo-Skok, O. (International Journal of Sports Medicine, 2015)
The aims of this study were to analyse the effects of eccentric overload training (EOT) on kinetic parameters during change of direction (COD) and performance related to sprinting and jumping abilities. 20 male soccer players performed 2 different protocols: 1) 5-min cycling warm-up and 2) 5-min cycling warm-up+YoYo half-squat exercise. The outcome measured included vertical ground reaction force (vGRF) and propulsive force (PvGRF), time to vGRF (T_vGRF) and propulsive force (T_PvGRF), contact time (CT), eccentric (ECC_IMP), concentric (CONC_IMP) and total (TOT_IMP) impulses and moments (Mx, My and Mz) during 2 COD tasks. Additionally, subjects performed a counter-movement jump (CMJ) and 20 m sprint tests. Results showed a substantial better improvement (likely to almost certainly) in vGRF (ES: 0.84), vAGRF (ES: 0.72), CT (ES: 0.48), My (ES: 0.35), Mz (ES: 0.44) and ECC_IMP (ES: 0.45) during crossover cutting maneuver, whereas during side-step cutting maneuver Time_ECC (ES: 0.68), CT (ES: 0.64), vGRF (ES: 0.48) and My (ES: 0.47) were substantially enhanced (likely). Furthermore, substantial better performance was found in CMJ (ES: 0.47; very likely) and 20 m (ES: 0.20; possibly). In conclusion, EOT produced a better muscle activation during 2 different COD tasks and greater sprinting and jumping performance.
Keywords: eccentric overload training; crossover cutting; side-step cutting; muscle performance; maximal power output